Health Education Using Puzzel Media About Hand Washing Behavior with Soap - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Indonesians' habit of washing their hands with soap is still relatively low. However, not washing hands with soap can cause several diseases, including diarrhea and upper respiratory tract infections, which result in impaired growth and development in children. One of the factors that influences hand washing behavior with soap is lack of knowledge. Efforts to increase knowledge that has an impact on the habit of washing hands with soap in children are by providing health education with interesting media and demonstrations. This community service aims to increase elementary school students' knowledge about washing hands with soap. The method used in this community service is health education using puzzle media and demonstrations. This health education activity was attended by 20 elementary school students as participants. The activity begins with a pre-test, and then the material is delivered using puzzle media, demonstrations, and questions and answers. To determine the effectiveness of health education activities on participants' knowledge about washing hands with soap, a post-test was carried out. The activity begins with a pre-test, and then the material is delivered using puzzle media, demonstrations, and questions and answers. To determine the effectiveness of health education activities on participants' knowledge about washing hands with soap, a post-test was carried out. It is hoped that the results of this health education will not only increase participants' knowledge but will also become a habit for elementary school children to wash their hands with soap before and after carrying out activities.